A Patient with Intermediate Syndrome with Toxic Encephalopathy Following Organophosphate Poisoning - Sharif, Mohiuddin; Bhuiyan, Muktadir; Roy, Rajib; Haque, Mahfuzul; Amin, Md Robed (Bangladesh Journal of Medicine, 2019)
OP poisoning is the common cause of mortality and morbidity in Bangladesh. Although acute cholinergic crisis is the common form of presentation of such cases, the intermediate syndrome and delayed encephalopathy can be also presented in op compound. A 14 year old adolescent presented with acute onset of intermediate syndrome and simultaneous early encephalopathy after ingestion of combination of Chlorpyrifos with Cypermithrin known popularly as market name of ‘Mortar’. The patient was provided supportive care and few days of ICU care with complete recovery. The interesting feature of the case was absence of cholinergic crisis and hence patient was not treated with atropine or pralidoxime.The simultaneous combination of presenting features, prolonged coma and even on absence of specific antidote complete recovery was the highlighting points of this unique case. Bangladesh J Medicine Jan 2019; 30(1) : 41-43